2021
DOI: 10.1002/brb3.2124
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms underlying the Rubber Hand Illusion: A systematic review of related neurophysiological studies

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Noninvasive brain stimulation studies showed that the activity in motor (della Gatta et al, 2016;Fossataro et al, 2018) and somatosensory (Zeller et al, 2015;Hornburger et al, 2019;Isayama et al, 2019) brain areas was attenuated during the experience of illusionary ownership over a rubber hand (i.e., during the synchronous but not asynchronous multisensory stimulation). These findings have previously been discussed as an indication for the disembodiment of the real hand necessary to embody a rubber hand (for a review see Golaszewski et al, 2021). The use of immersive VR with highly congruent visuo-motor and proprioceptive feedback -compared with the rubber hand illusion, no proprioceptive mismatch is present-may allow to induce highly realistic illusions, without the necessity for the user/brain to disembody the own limbs.…”
Section: The Strength Of Subjectively Experienced "Stone Arm Illusion...mentioning
confidence: 76%
See 1 more Smart Citation
“…Noninvasive brain stimulation studies showed that the activity in motor (della Gatta et al, 2016;Fossataro et al, 2018) and somatosensory (Zeller et al, 2015;Hornburger et al, 2019;Isayama et al, 2019) brain areas was attenuated during the experience of illusionary ownership over a rubber hand (i.e., during the synchronous but not asynchronous multisensory stimulation). These findings have previously been discussed as an indication for the disembodiment of the real hand necessary to embody a rubber hand (for a review see Golaszewski et al, 2021). The use of immersive VR with highly congruent visuo-motor and proprioceptive feedback -compared with the rubber hand illusion, no proprioceptive mismatch is present-may allow to induce highly realistic illusions, without the necessity for the user/brain to disembody the own limbs.…”
Section: The Strength Of Subjectively Experienced "Stone Arm Illusion...mentioning
confidence: 76%
“…However, the ability of the brain to adapt motor commands based on a perceived modified reality has not yet been fully explored. Evidence suggests that the embodiment over an artificial limb may go in line with the disembodiment of the own limb (for a review see Golaszewski et al, 2021 ). Previous neurophysiological studies using non-invasive brain stimulation techniques (transcranial magnetic and direct current stimulation) and electroencephalography (EEG) have evidenced attenuated activity in motor ( della Gatta et al, 2016 ; Fossataro et al, 2018 ) and somatosensory ( Tajadura-Jiménez et al, 2012 ; Zeller et al, 2015 ; Hornburger et al, 2019 ; Isayama et al, 2019 ; Sakamoto and Ifuku, 2021 ) brain areas, along with enhanced error tolerance ( Raz et al, 2020 ) during the experience of illusionary body ownership.…”
Section: Introductionmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) can also be used to study the link between neural activity in the sensorimotor cortical network and the experience of body ownership. TMS can be applied to the primary motor cortex during an embodiment illusion to create motor evoked potentials on demand (della Gatta et al, 2016 ; Karabanov et al, 2017 ; Isayama et al, 2019 ; Golaszewski et al, 2021 ). Then, electromyography (EMG) measured on the target limb can quantify the motor excitability of the corticospinal circuits during the illusion.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…However, we cannot ignore the influence of sensory representations on motor function and the sensorimotor network when considering motor control and motor rehabilitation. Phenomena such as the rubber hand illusion ( 26 , 27 ) and the mirror synaesthesia ( 28 , 29 ), and phantom limb sensations ( 30 ) illustrate that sensory representations can also be embodied. Studies of phantom limb phenomena show that individuals continue to have awareness and experience sensations of bodily unity and continuity despite actual sensory and motor loss ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%